MEMAHAMI KENABIAN YEREMIA DAN KITABNYA - Elisamark Sitopu (Jurnal Teologi Cultivation, 2019)
Abstract[Title: Understanding Jeremiah’s Prophecy and His Book] Jeremiah is a prophet in the Old Testament, whose book is thick with a maximum biography. To understand the message of the prophet of Jeremiah, the readers must recognize two important things. First, the prophet Jeremiah himself, and the second,the book of Jeremiah. On one hand, there are frictions between Old Testament scholars about the historicity of Jeremiah's own figure. Is the figure of Jeremiah real or not real? On the other hand, there are many problems regarding the book of Jeremiah, related to the author of the book of Jeremiah. Who was the author of this book?Was it Jeremiah himself, or his secretary Barukh,orsomeone else, or later editors?Other problems related to the text about large differences in Jeremiah's text in the Hebrew and Greek versions of the Bible are very striking. In this study the author intends to provide an alternative solution to the complexity of Jeremiah's figure and his book.Keywords: Prophet Jeremiah, Book of Jeremiah